2018
DOI: 10.1167/iovs.18-23935
|View full text |Cite
|
Sign up to set email alerts
|

Aldose Reductase Inhibition Prevents Development of Posterior Capsular Opacification in an In Vivo Model of Cataract Surgery

Abstract: PurposeCataract surgery is a procedure by which the lens fiber cell mass is removed from its capsular bag and replaced with a synthetic intraocular lens. Postoperatively, remnant lens epithelial cells can undergo an aberrant wound healing response characterized by an epithelial-to-mesenchymal transition (EMT), leading to posterior capsular opacification (PCO). Aldose reductase (AR) inhibition has been shown to decrease EMT markers in cell culture models. In this study, we aim to demonstrate that AR inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 47 publications
5
39
0
Order By: Relevance
“…Cadherins (E-, N-, P- and R-cadherin), a family of calcium-dependent cell adhesion molecules, share a high degree of structural similarity which undergo homophilic interactions to maintain cell-cell contacts at adherens junctions [36]. It has been shown in embryonic stages of double mutant mice that E− and N-cadherin play an essential role during lens vesicle separation [37] Our results support earlier results that E-cadherin plays a critical role in the lens development and that it lost after 5 days in wild type mice [38]. N-cadherin which is a marker for mesenchymal cells was present at the site of cell-cell contact.…”
Section: Discussionsupporting
confidence: 88%
“…Cadherins (E-, N-, P- and R-cadherin), a family of calcium-dependent cell adhesion molecules, share a high degree of structural similarity which undergo homophilic interactions to maintain cell-cell contacts at adherens junctions [36]. It has been shown in embryonic stages of double mutant mice that E− and N-cadherin play an essential role during lens vesicle separation [37] Our results support earlier results that E-cadherin plays a critical role in the lens development and that it lost after 5 days in wild type mice [38]. N-cadherin which is a marker for mesenchymal cells was present at the site of cell-cell contact.…”
Section: Discussionsupporting
confidence: 88%
“…The control group received 25 mM SPB alone. Mice consumed 3. to immunofluorescence detection of α-SMA (1:100 dilution) and collagen type IV (1:100 dilution, Sigma, Cat# 9272), as previously described [43].…”
Section: Effect Of Aspirin On the Emt Of Lecs In Lensectomized Micementioning
confidence: 99%
“…In addition to the change of cell shapes, the common EMT markers include α-smooth muscle actin (α-SMA), fibronectins, and vimentin, and the reduction of these markers showed that EMT was inhibited. Zukin et al [29] selected the aldose reductase (AR) transgenic mice as the AR overexpression model and found that AR overexpression could increase the level of α-SMA and fibronectins in mice LECs via real-time Polymerase Chain Reaction (PCR), which reflected that AR overexpression activated LECs' EMT. After adding AR inhibitor Sorbinil, they observed the decline in the level of α-SMA and fibronectins, which meant the EMT of LECs was inhibited.…”
Section: Signaling Pathways On Lecs' Emtmentioning
confidence: 99%